Strategi Adaptasi Industri Batik Tulis di Kawasan Seberang Kota Jambi - Rizal, Azira Novia; Rahmadani, Suci; Putri, Revi Jeane (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
This article discusses the strategy of batik Jambi industry owners to maintain existence in community. As a superior regional product, this industry has fluctuation of Jambi batik craftsmen in recent years as well as high competition with batik craftsmen from Java Island with cheaper prices. The research was conducted in Danau Teluk District and used a qualitative method with a case study design. The finding of this research is showed that there are four strategies in Batik Jambi industry. First, the successive investment strategy that the selection of workers according to certain criteria and there is participation of families involved in the Batik Jambi industry. Second, the educational investment strategy is the owners of industry, craftsmen and the government collaborate through training and outreach programs and produce more varied and innovative products. Third, the economic investment strategy, that is by utilizing economic and social capital and innovating marketing techniques that are currently more easier to public. Fourth, a symbolic investment strategy that is seen in the efforts of industrial owners to improve the quality of their products so it can be improves sales and customer satisfaction.